Stocker Steer Gains and Fly Numbers as Impacted by Burn Date and Type of Mineral on Tallgrass Native Range – Year 3 - J. K. Farney; M. Frahm (Kansas Agricultural Experiment Station Research Reports, 2022)
This study aims to evaluate effectiveness of two operational management systems for steer gains and fly control. The first strategy evaluated was pasture burn date of March (MAR) or April (APR). The second management strategy was free-choice mineral with spices (SPICE) or without spices (CON). Eight pastures (n = 281 steers; initial weight 572 ± 75 lb) were used in a 2 × 2 factorial treatment structure. Steers were weighed individually, randomly assigned to treatment, and grazed for 87 days. Weekly, 33% of steers were photographed to count flies and evaluated for hair coat score. Neither the date of pasture burning nor the mineral type impacted cattle gains for all treatments. Cattle consuming mineral with spices had less flies through a majority of the grazing period. Even though SPICE cattle had less flies, the spice treatment did not result in improvements in gain as during the weeks where spice cattle had less flies than control, both treatments were over the economic threshold for horn flies (200 flies per steer). Additional years on this project will be completed to determine the effects of pasture burn date and addition of spices in mineral.
Keywords: essential oils; spices; growth; ectoparasite